Pengaruh E-Commerce terhadap Minat Belanja Mahasiswa FEBI - Ainun Nufus; Anggita Mujayanah; Athfiatul Asfiyah; Wahyu Hidayat; Hadi Peristiwo; Fitri Fitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The rapid growth of e-commerce has significantly transformed consumer behavior, particularly among university students. This study examines how e-commerce platforms affect the interest and shopping preferences of students of the Faculty of Economics and Islamic Business, UIN Sultan Maulana Hasanuddin Banten. By analyzing data from surveys conducted among students, the research identifies key factors that drive their engagement with online shopping. These factors include convenience, variety of products, competitive pricing, and the ease of comparing different products. The study also highlights the role of technological advancements, such as mobile applications and secure payment gateways, in enhancing the online shopping experience. Furthermore, it explores the psychological aspects, such as the excitement of online deals and the influence of social media advertising, on students' shopping habits. The findings suggest that e-commerce has not only increased the frequency of students' purchases but also diversified their buying patterns. However, the study also addresses potential challenges, such as the risk of overspending and the impact of impulsive buying. Overall, the research provides valuable insights into the evolving landscape of consumer behavior in the digital age, emphasizing the importance of e-commerce in shaping the shopping interests of the younger generation.